1996
DOI: 10.1289/ehp.96104s3629
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aneuploidy in human spermatozoa of normal semen donors by fluorescence In situ hybridization

Abstract: We have studied human spermatozoa from 24 normal, healthy unexposed men, 18 of whom were semen donors at the Sperm Bank in Turku, using multicolor fluorescence in situ hybridization with two chromosome-specific probes. The possible age-related increase in aneuploidy frequencies was assessed. Ten thousand spermatozoa were scored per individual for the presence of hyperploid, i.e., disomic and diploid, cells. The overall hybridization efficiency was 98.8%. The frequency of spermatozoa with two chromosome 1 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
6
1
Order By: Relevance
“…If the conservative estimate of aneuploidy (aneuploidy = 2 × hyperhaploidy) is applied, our results indicate that the frequency of aneuploid sperm in boars is approximately 3 %. Thus, the observed level of numerical chromosome aberrations in boar sperm appears to be within the baseline range reported to date for men (Holmes and Martin, 1993;Robbins et al, 1995;Lähdetie et al, 1996;Spriggs et al, 1996;Rademaker et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…If the conservative estimate of aneuploidy (aneuploidy = 2 × hyperhaploidy) is applied, our results indicate that the frequency of aneuploid sperm in boars is approximately 3 %. Thus, the observed level of numerical chromosome aberrations in boar sperm appears to be within the baseline range reported to date for men (Holmes and Martin, 1993;Robbins et al, 1995;Lähdetie et al, 1996;Spriggs et al, 1996;Rademaker et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…Baumgartner et al (1999) suggested that the use of two probes might be a more reliable measure of chromosome disomy than hybridization with a single probe. Various studies found evidence of significant interindividual heterogeneity (Griffin et al, 1995;Lahdetie et al, 1996;Spriggs et al, 1996;Kinakin et al, 1997) for disomy frequency of all studied chromosomes. There is also evidence for stable intraindividual sperm aneuploidy frequencies.…”
Section: Chromosome Abnormalities Found By Fluorescence In Situ Hybrimentioning
confidence: 94%
“…Another study by Martinez-Pasarell et al [1999] investigated the paternal age effect of chromosome 6 disomy in fathers of children with Turner syndrome and did not see paternal age effect on chromosome 6 disomy. Lahdetie et al [1996] reported that the frequency of chromosome 7 sperm disomy was not significantly different between younger and older donors; however, donor age was no more than 46 years. Similarly, Schmid et al [2004] also did not reveal any agerelated pattern associated with chromosome 7 sperm aneuploidy [Guttenbach et al, 1994[Guttenbach et al, , 1997.…”
Section: Fish Studies Autosome By Autosomementioning
confidence: 95%
“…Similar studies, however, have not found such a correlation: McInnes et al [1998] hybridised 2 probes from chromosome 1 (centromeric and 1p midi-satellite) and reported that the frequency of disomy was not influenced by donor age, but there was an age-related association of acentric fragmentation of chromosome 1. Lahdetie et al [1996] also reported that there was no statistically significant correlation between age of the donors (range 20-46 years) and the frequency of disomic sperm, nor did Guttenbach et al [1997Guttenbach et al [ , 2000. One reported criticism of the work by Martin et al [1995] was that it used a probe for the large heterochromatic region at 1q12 that may be more prone to breakage in sperm heads (perhaps in relation advanced age) Schmid et al, 2004].…”
Section: Fish Studies Autosome By Autosomementioning
confidence: 99%